Simulations of full-time employment and household work in the Levy Institute Measure of Time and Income Poverty (LIMTIP) for Argentina, Chile, and Mexico - Thomas Masterson (Levy Economics Institute of Bard College, 2012)
The method for simulation of labor market participation used in the LIMTIP models for Argentina, Chile, and Mexico is described. In each case, all eligible adults not working full-time were assigned full-time jobs. In all households that included job recipients, the time spent on household production was imputed for everyone included in the time-use survey. The feasibility of assessing the quality of the simulations is discussed. For each simulation, the recipient group is compared to the donor group, both in terms of demographic similarity and in terms of the imputed usual hours, earnings, and household production produced in the simulation. In each case, the simulations are of reasonable quality, given the nature of the challenges in assessing their quality.
Keywords: C14; C40; D31; J22; 330; Labor Force Simulation; Time Use; Household Production; Poverty; LIMTIP; Argentina; Chile; Mexico